Analisis Rendahnya Kualitas Pendidikan di Indonesia Saat Ini : Suatu Kajian Literatur - Dzaky Satria; Ihsan Hutama Kusasih; Gusmaneli Gusmaneli (Pusat Riset dan Inovasi Nasional, 2025)
Education is a paramount aspect of a nation's development. It is a right that every individual within a country must obtain. Through education, a nation can easily achieve progress due to its competent human resources. Developed countries undoubtedly possess high-quality education. This research will examine the current state of education quality in Indonesia. This study employs a library research method, analyzing existing scientific sources such as books, journals, and other information. The research reveals that the level and quality of education in Indonesia are still low. This is evident in the numerous shortcomings in the implementation of education in Indonesia, such as the lack of competent teachers, limited facilities and infrastructure, unequal distribution of education between urban and rural areas, and many more.